In The Mid of Closure Lies Opportunity: Live Experiences of the Tourism Displaced Workers - A. Mijares, Leigh Anne; G. Rodriguez, Darryl (International Journal of Scientific Research and Management (IJSRM), 2021)
Boracay Island, Philippines is known for being a world’s beach destination.  However, rapid infrastructures development and wanton disregard to the physical environment eventually lead to a six-month temporary closure of the Island for rehabilitation purposes based on Presidential Proclamation No. 475.  As a consequence, emergence of displaced workers in the Island occurred. In this paper, the researchers aimed to know the perceptions of the displaced workers in terms of their stances, feelings and opportunities relative to the issue. The researchers used Phenomenological study, a qualitative research, to deeply know the lived experiences of the displaced tourism workers in Boracay. Key informants were selected through purposive sampling. This study evinced that the displaced workers carry on their indomitable spirits of survival. Hence, the displaced workers were amenable of the closure of the Island for the preservation for the next generation. Moreover, they established business in their respective places, while others are looking for new opportunities. Nevertheless, they still have plans to go back to the Island because of innermost and better opportunities that await them. It is strongly recommended that all stakeholders must strictly enforce environmental laws owing to the fact that the main attraction of Boracay is their pristine nature; without it, everything about Boracay goes nil.